Electrochemical mechanism of CO2 reduction mediated by NiII(tpa) (tpa = tris(2-pyridylmethyl)amine) complexes: An integral view. (20th December 2021) - Rebolledo-Chávez, Juan Pablo F.; Cruz-Ramírez, Marisela; Ramírez‐Palma, David I.; Ocampo-Hernández, Janet; Mendoza, Angel; Cortés-Guzmán, Fernando; Ortiz-Frade, Luis
Highlights: Full characterization of Ni II ( tpa ) complexes gives information about its electronic structure which corelates with electrochemical behavior. Ni II ( tpa ) complexes presented tunable redox potential for the Ni II /Ni I reduction. Ni II complex with more negative redox potential presented the high catalytic activity for CO2 reduction. Theoretical approach was useful for the analysis and description of electrochemical mechanisms. Abstract: In this paper, we report the synthesis, characterization, as well as electrochemical, spectroelectrochemical, and density functional theory (DFT) calculations of a series of novel Ni II complexes with a flexible tetradentate ligand, tris(2-pyridylmethyl)amine) ( tpa ). The complexes [Ni II ( tpa )(H2 O)(MeCN)](BF4 )2, [Ni II ( tpa )(NO3 )2 ], and [Ni II ( tpa )Cl2 ] were studied for their ability to electrochemically reduce CO2 . These complexes were compared with the tris-chelate complex [Ni(bpy)3 ](BF4 )2 to understand the role of flexible tetradentate ligands containing a pyridinic ring in the electrochemical reduction of CO2 . Spectroelectrochemical experiments and theoretical studies were performed to rationalize the electrochemical reductions occurring and to predict the redox potential and pathway of CO2 reduction. Graphical abstract: The electrochemical behavior of Ni(II) complexes with the ligand tris(2-pyridylmethyl)amine) was studied, in order to explore its ability to reduce electrochemically CO2 . Theoretical studies allowed to rationalize where the electrochemical reductions occur and predict redox potential and the pathway of CO2 reduction. Image, graphical abstract